Control above social services of civil society - Valentine Sanzharovets; Maria Panchenko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
Civil society must be active, to control realization of social services, because it is the customer of quality social work. Choice of professional social help will help to overcome negative consequences the clients of social work at local level in Ukrainian society. Urgent is a requirement increation of nontate social services that can compete at the market of social services.
Keywords: social services; civil society; social policy